Mexico : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Selected Issues paper is a wide-ranging survey of the conditions for, and obstacles to, the growth in Mexico. It frames the issue of Mexico's growth record, and presents the paper's prior assumptions and approach. It highlights the main observations and conclusions emerging from the survey of growth conditions in Mexico. It also presents an overview of remittances in Mexico, motivated by their recent increase and possible macroeconomic implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet